Workplace violence, psychopathological symptoms, and deviant workplace behavior among nursing interns in China: a network analysis - Simeng Dong; Xinshu Shen; Tong Zhao; Rui Zeng; Min Chen (BMC Nursing)
Abstract Background Workplace violence in healthcare has become a global concern, and nursing interns are not immune to it in clinical settings. It is critical to understand the impact of workplace violence on the psychological and work status of nursing interns. Methods Between April and May 2024, a total of 2213 nursing interns from 12 hospitals in China participated in the study. Data were collected with questionnaires on basic information, the Workplace Violence Scale, the Caregiver Occupational Deviant Behavior Scale, and the DSM-5 Level 1 Cross-Cutting Symptom Measure. The basic analysis was performed using SPSS 24.0 software, and the network structure analysis was constructed using R software to calculate the relationship between the nodes and the centrality index. Results In nursing interns, the items with the highest prevalence of workplace violence were verbal assault (32.038%) and threats (10.303%); in psychopathological symptoms, the items with the highest prevalence were anxiety (38.500%), anger (35.337%), and depression (33.439%). The strongest edge within the cluster is “Verbal sexual harassment-Physical sexual harassment,” and the strongest edge between clusters is “Verbal assault-Depression.” The node with the highest strength, expected influence, and betweenness indices is “Anxiety,” and the node with the highest closeness index is “Depression.” Conclusions The results demonstrate the effectiveness of the network perspective in elucidating the complex relationships and interconnections between different symptoms. We identified the strongest relationships between nodes, “Depression” and “Anxiety” as the most important symptom. These findings may provide more precise targets for developing interventions for nursing interns.